Mastering critical thinking skills is strongly associated with the ability to recognize fakeness and misinformation - Redaelli, Simone; Biller-Andorno, Nikola; Gloeckler, Sophie; Brown, Jessica; Spitale, Giovanni; Germani, Federico (Frontiers in Education, 2025)
IntroductionIn the current era of digital information overload, individuals are inundated with content of varying quality and truthfulness. Critical evaluation of such content is essential to distinguish between legitimate information and misinformation or fakeness. Despite this need, there is limited empirical evidence on the effectiveness of training in critical thinking skills for enhancing such discernment.MethodsThis study operationalized critical thinking into six measurable concepts: causation and correlation, independent data and replicates, reproducibility, credibility of sources, experimental control, and statistical significance. A pre-registered randomized controlled trial was conducted involving educational video interventions aimed at improving participants’ understanding and application of these concepts. Participants were evaluated based on their ability to identify fake tweets and misinformation both before and after the intervention.ResultsA strong correlation was found in the pre-intervention phase between mastery of critical thinking concepts and the ability to identify misinformation and fakeness. However, the video-based intervention did not significantly enhance critical thinking skills nor improve the participants’ accuracy in identifying misinformation compared to the control group. The intervention’s inefficacy was consistent across various demographic and educational backgrounds.DiscussionThe findings suggest that while mastery of critical thinking is associated with greater resilience against misinformation, current educational interventions—such as short video lectures—are insufficient. There is a pressing need to develop and empirically validate more effective, possibly interactive, training modalities that can foster misinformation-specific critical thinking skills in the general population.